Entrepreneurship Snapshots 2010 : Measuring the Impact of the Financial Crisis on New Business Registration. - Bank, World (World Bank Publications, 2010)
The 2010 World Bank Entrepreneurship Snapshots (WBGES) provide a unique indicator of business creation around the world and facilitate the investigation of the factors that foster dynamic private sector growth. Now in its fourth year, the WBGES measure entrepreneurial activity in 115 developing and industrial countries over the six year period 2004-2009. Importantly, the data offer a distinctive and timely snapshot of the impact of the 2008-2009 financial crisis on entrepreneurial activity. There is wide variation in new business creation across countries: On average, about four new firms regi.